Problematik dan Krisis Pendidikan Islam - Suhartini khalik; Syarifuddin Ondeng; Saprin, Saprin (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to describe the problematic and crisis of Islamic education, encompassing the issues faced by contemporary and future Islamic education, the challenges posed to Islamic education in the present and future, and alternative solutions to the issues of current and future Islamic education. The study adopts a qualitative research approach utilizing literature review (library research), with books and other literature as the main focus of the research. The literature obtained from various references is critically and comprehensively analyzed to support the propositions and ideas presented in the research.The challenges faced by contemporary Islamic education include the deterioration of the pillars of character education, the existence of Islamic educational institutions such as pesantren and madrasah that need to develop their curriculum to meet the demands of the times, among other issues. Specific challenges involve educational management aspects, where future education planning needs to encompass three fundamental aspects of society: socio, techno, and bio futures, with all implications and impacts on human life.Particularly for pesantren, there is a challenge in addressing the progress of Science and Technology (Iptek), Western culture, and unfounded accusations directed towards Islamic boarding schools. Alternative solutions proposed include a new paradigm for Islamic education based on both the theocentric and anthropocentric philosophies. Islamic education should be capable of building scholarly and progressive educational integration of spiritual, moral, and material values for human life. Additionally, Islamic education should emphasize a more flexible structure, treating students as individuals in constant development, and consistently interacting with the environment.